Optimalisasi Pengelolaan Sampah di TPS 3R Randu Alas sebagai Upaya Mitigasi Bencana Hidrometeorologi - Afif Ari Wibowo (Abdi Geomedisains, 2025)
The Randu Alas Waste Management Site (TPS), located in the upstream area of the Opak Watershed, Sleman, has faced major challenges since the closure of the Piyungan Landfill, which forced the TPS to independently manage residual and organic waste. Residual waste continues to be burned, contributing to air pollution, while organic waste cannot be processed into compost due to limited facilities and human resources. In addition, non-customer households still burn waste, and customer households have not consistently implemented sorting, resulting in increased volumes of mixed waste entering the TPS. The use of open trash bins also increases the proportion of wet waste and allows some waste to be carried into waterways. This community service program aims to (1) develop more environmentally friendly waste management practices and (2) strengthen public education on sorting as a strategy to mitigate hydrometeorological disasters. The activities implemented include education on waste sorting, provision of separated and closed trash bins, campaigns on the dangers of burning waste, training on organic waste processing into compost, and training on managing residual waste using a mini incinerator. The results showed improved community knowledge, availability of sorting facilities in households, and initial compost production by residents. More than 50% of training participants have begun sorting waste at home, and the practice of burning waste in residential yards has been eliminated. The TPS has also adopted a new method for handling residual waste through the use of a mini incinerator. Overall, these activities enhance community capacity to reduce air pollution and support efforts to mitigate hydrometeorological disaster risks in upstream watershed areas. The next potential program is the development of a circular economy based on sorted waste.